Membincang Akulturasi Pernikahan: Makna Tradisi Mapacci Pada Pernikahan Adat Suku Bugis Makasar - Hartini, Dwi; Ilhami, Nuzula; Taufiqurohman, Taufiqurohman (Tasyri' : Journal of Islamic Law, 2022)
This paper discusses the wedding tradition which has various versions in the process according to the culture and context in which the marriage is carried out. The wedding tradition in question is a series of processions leading to marriage. One of the unique wedding processions is the Bugis traditional wedding called Mapacci. This Mapacci tradition is interesting to study in relation to the perspective if it is seen from the difference in social stratification in its implementation between the nobility or ordinary people. This paper is studied using the theory of Semiotics of Charles Sanders Peirce, according to Peirce, human life is characterized by the mixing of signs and how they are used in representative activities. The social system is related to the integration function by controlling the components that make up society, finally the cultural system is related to the function of maintaining existing patterns or structures by setting up norms and values ​​that motivate them to take an action. The results of the study indicate that the meaning contained in the traditional mappacci process is a form of hope and prayer, for the welfare and happiness of the prospective bride and groom which is combined in a summary of words (mappacci) of 9 kinds of equipment that must be prepared and moved not only for the nobility but all the indigenous people of Bugis.